Hospital-at-home care in Singapore: A qualitative exploration of health system partners’ state of readiness, and policy and implementation strategies essential to support scale-up - Crystal Min Siu Chua; Eward Wei Zheng Lim; Win Hon See Tho; Yuka Asada; Karen E. Peters; Yi Feng Lai (PLoS ONE, 2025)
Rationale Many Hospital-at-Home (HaH) programs have proliferated in recent years to cope with the increasing demands of an ageing population and global hospital bed shortages. Singapore has implemented its own version, Mobile Inpatient Care at Home (MIC@Home). However, many HaH programs remain small, raising concerns about their scalability. Hence, a clear implementation strategy is needed. Objectives To address: (1) What is the readiness of Singapore’s health system partners to scale up MIC@Home? and (2) What multi-level strategies are necessary for the successful scaling of MIC@Home in Singapore?. Methods A descriptive qualitative study design was used. Through purposive sampling, 32 participants (16 HaH clinicians, 11 enabling units, and 5 regulators) were recruited and semi-structured interviews were conducted. The interviews were transcribed using Trint and thematically analysed using Atlas.ti via Braun and Clarke’s six-step inductive approach. This analysis was guided by the Health Policy and Partnership Readiness Assessment Framework. Results The key themes were: (1) perceived readiness to scale, focusing on stakeholder motivation and capacity; (2) implementation strategies, highlighting the need for training, collaborations, and operational refinements; and (3) policy strategies, addressing financial sustainability, governance, and regulation. MIC@Home is seen as a viable solution to acute bed shortages, with high readiness for scaling. Effective governance requires stakeholder buy-in, organizational alignment, partnerships, and adequate manpower. Regulatory strategies should be adjusted to sustain MIC@Home and improve patient access. For service provision, standardized guideline and data is vital to prove MIC@Home’s effectiveness and safety, while convincing clinicians and patients of its value will increase acceptability. Finally, refining governance and establishing regulations for minimum care standards will support smooth operations and long-term success. Conclusion Despite the challenges of scaling MIC@Home, the findings underscore the potential of MIC@Home to enhance healthcare delivery through identifying readiness and strategies to position MIC@Home as an alternative to traditional care.